Cellulose Derivative-Based Bioadhesive Blend Patch for Transdermal Drug Delivery - Manna, Sreejan; Dhanalakshmi, Dadala; Bhowmik, Manas; Jana, Sougata; Jana, Subrata (Frontiers in Materials, 2022)
In this study, matrix type transdermal patches of glibenclamide were developed using a combination of hydrophilic and hydrophobic polymers. A cellulose derivative, HPMC E50 was used as a hydrophilic matrix forming polymer, and Eudragit RS 100 was used as a hydrophobic polymer. No drug- polymer interaction was observed by FTIR study. The membrane permeation study exhibited a sustained release of glibenclamide depending on the polymeric ratio. The increased concentration of Eudragit RS 100 in different formulations has gradually decreased the amount of drug penetration through the membrane. The kinetic analysis showed the release is best explained by zero order kinetics, followed by Higuchi and first order. The release exponent suggested a shifting of non-Fickian diffusion to super case II transport drug release mechanism when Eudragit RS 100 concentration was increased. It is concluded that the developed formulations may be a better alternative to the conventional oral delivery of glibenclamide.